FIRST RANK SYMPTOMS IN THE DIAGNOSIS OF SCHIZOPHRENIA - Idrees, Muhammad; Khan, Imran; Irfan, Muhammad; Sarwar, Robina (Journal of Postgraduate Medical Institute, 2011)
Objectives: Methodology: Results: Conclusions: The reliability of the presence of first rank symptoms in Schizophrenia should be taken cautiously as only one third of the patients diagnosed with schizophrenia as per the DSM IV criteria showed any first rank symptom. Out of 100 patients suffering from schizophrenia, there were 58 males and 42 females. Thirty four (34%) (22 male & 12 females) reported having one or more first rank symptoms while Sixty six (66%) patients although diagnosed with schizophrenia on DSM IV criteria did not show first rank symptoms. The most often found individual first rank symptoms in these 34 patients were voices commenting (n=14, %), made impulses (n=12, %), and voices arguing (n=12, %). None reported delusional perception. Patients suffering from schizophrenia, admitted to the Psychiatry Ward Khyber Teaching Hospital, Peshawar during the year 2009 were selected by non probability purposive sampling. It was a descriptive study and the diagnosis was made according to DSM-IV criteria. Patients were interviewed by using a semi structured questionnaire based on Present State Examination and first rank symptoms were assessed. To determine the usefulness of Schneider's first rank symptoms of schizophrenia.